Examining the impact of environmental centralization on enterprise total factor productivity through a quasi-natural experiment conducted in China - Chen, Aonan; Cheng, Yangyang (Scientific reports, 2024)
This paper explores the effects and influence mechanisms of environmental centralization on enterprise technological progress and productivity in China. Taking the reform of vertical environmental governance (VEG) as a quasi-natural experiment, this paper compares the differences in total factor productivity (TFP) of enterprises in environmental centralization regions and environmental decentralization regions by adopting the staggered difference-in-differences (DID) method. The empirical results show that: (1) The average TFP of enterprises in the environmental centralization areas is 0.0598 higher than that in the environmental decentralization areas, and this average effect increases with the extension of the reform duration. (2) Environmental centralization strengthens government intervention in environmental issues. The improvement in the intensity of environmental regulation and the willingness of firm green innovation are the intermediate causes of the improvement in enterprise TFP. (3) VEG’s effect is heterogeneous regarding regional development, industry type, and enterprise characteristics. This study has empirical implications for further refining the fiscal system to leverage the role of public finance on environmental governance and enterprise development.